1997
DOI: 10.1002/(sici)1096-9888(199711)32:11<1195::aid-jms578>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of urinary acylcarnitines by ESI-MS coupled with solid-phase microextraction (SPME)

Abstract: The determination of selected short‐, medium‐ and long‐chain acylcarnitines by electrospray ionization mass spectrometry (ESI‐MS) is discussed. The differences in fragmentation behaviour and ionization efficiency are described in dependence on collision induced dissociation (CID) conditions and mixture composition. A new method combination, solid‐phase microextraction (SPME)‐ESI‐MS, is introduced to characterize acylcarnitines in body fluids. This method utilizes SPME for pre‐concentration of acylcarnitines fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Approximately 150 spectra of different libraries of compounds were studied. The following groups of molecules were investigated: sulfonamides,20–36 benzimidazoles,37–48 carnitines,49–54 amphetamines,55–60 amino acids,61–80 and purines 81–83. It was observed that each of the above groups produced specific fragment ions and neutral mass losses, depending on the functional groups present in the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 150 spectra of different libraries of compounds were studied. The following groups of molecules were investigated: sulfonamides,20–36 benzimidazoles,37–48 carnitines,49–54 amphetamines,55–60 amino acids,61–80 and purines 81–83. It was observed that each of the above groups produced specific fragment ions and neutral mass losses, depending on the functional groups present in the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…More evaluation parameters concerning the determination of acylcarnitines by FIA-ESI-MS have been reported previously [15]. The results of this method evaluation were the basis for the interpretation of all MS values determined.…”
Section: Resultsmentioning
confidence: 83%
“…The influence of solvent and matrix accompanying the target analytes has been discussed previously [15]. Despite ion-suppressing effects of the urine matrix the typical target ions can be detected; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By combination Fig. 1 Procedure of extraction by fiber SPME and desorption for GC and HPLC analyses with HPLC [29,30,31,32,33,34,35,36,37,38,39,40,41,42] and LC-MS [43,43,44,45,46,47,48,49], it has been applied to the analysis of various polar compounds such as drugs and pesticides. These SPME methods are based on the adsorption of compounds by the liquid phase coated on the surface of the fiber.…”
Section: Hiroyuki Kataokamentioning
confidence: 99%